Climate Change and Geopolitics: A Conflict in the Arctic - Covino, Lisa (Université Saint-Paul / Saint Paul University, 2018)
This thesis is focused on the redefinition of the Canadian domestic and foreign Arctic policies based on a model of sustainability and sustainable development customized for the Arctic region. More specifically, since the beginning of the nineteenth century, the Arctic has become a pivotal region in terms of energy resources and economic opportunities due to the influence of the effects of climate change on the region. In fact, climate change is considered the prime trigger of ecological phenomena such as raising of the average seasonal temperatures, thawing of the sea ice and dysfunctional patterns of precipitations. As a result, fundamental ecological mechanisms determining the equilibrium and survival of the ecosystem, such as the albedo effect, are affected, producing alterations in the ecosystem’s biodiversity and physical composition. Therefore, this thesis will focus on the causal relationship that links climate change with both ecological changes and geopolitical and economic opportunities. First, I will analyze this region from an ecological perspective, thus I will define the Arctic as an ecosystem, which means a systemic unit in the planetary environmental system of ecological mechanisms. Through the theory of tipping points, I will demonstrate the crucial role played by the stability of this region in the determination of planetary wind and oceanic currencies. Then I will focus my attention on the great availability of natural and energy resources in the region. I will consider Canada and the Canadian North as a case study to understand the importance of the Arctic physical composition in the determination of domestic and foreign policies. In fact, the increasing global demand for energy resources and the potential opening of a faster and larger international shipping route compared to the Panama Canal make the Arctic at the centre of global economic policies. For this reason, Canada is trying to obtain a globally recognized leading position in the research about the effects of climate change in the region and internationally recognized sovereign borders in the North. Finally, after having understood and described the region’s ecological vulnerabilities and the main Canadian interests in the North, I will develop a customized model of sustainable policy making for the region. I will ground my model on the theories of sustainability science and geoeconomics. I will achieve a deep understanding of the major Canadian economic objectives, describing them in sustainable terms, which means that I will define the set of parameters, such as public investments, necessary to make an economic policy as much ‘environmentally harmless’ as possible. My objective is determining a new Canadian model of sustainable policymaking, aimed at the protection and development of the North.
Keywords: climate change; Canadian Arctic; sustainability; sustainable development; polar geopolitics; Arctic sovereignty; geoeconomics